PROFIL GELATINISASI DAN KOMPONEN ANTIOKSIDAN TEPUNG KETAN HITAM TERMODIFIKASI DENGAN ANNEALING - Riezka Zuhriatika Rasyda; Tjahja Muhandri; Slamet Budijanto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2020)
This research aims to study and characterize the effect of the annealing conditions (temperature and heating duration) on the gelatinization profile and antioxidant components of annealing-modified black glutinous rice flour (ABGRF). This experiment used a 2x3 factorial design consisted of temperature factor (54 and 58°C) and heating duration factor (4, 5, and 6 hours) with 2 replications. Research results showed that both factors and their interactions significantly affected all parameters of the gelatinization profile and antioxidant component of ABGRF (except through viscosity). Compared to its native, ABGRF showed an increase in peak viscosity, through viscosity (except treatment 54°C:5 hours), peak time and pasting tem-perature, indicated ABGRF resistance improvement to the heating process. Generally, the temperature treatment increment increased breakdown, setback, and final viscosity, but the heating duration increment decreased those values. The variation of ABGRF gelatinization profiles increased the diversification potential of BGRF-based food products. Annealing caused an overall decrease in ABGRF antioxidant ability. ABGRF produced by 54°C:4 hours treatment had the highest amount of antioxidant components (total anthocyanins contents 103.78±2.24 mg C3GE/100 g, total phenolic compounds 241.65±1.98 mg GAE/100 g, DPPH 267.14± 3.23 mg AAE/100 g, FRAP 473.94±1.43 mg AAE/100 g), thus using it as ingredients in functional food is more recommended, especially as composite flour for bread and cake.